A mechanisms‐based reliability model for fatigue of composite laminates. Issue 10 (11th May 2015) - Talreja, Ramesh; Altenbach, Holm; Čate, Andris; Petrova, Vera; Talreja, Ramesh
<x xml:space="preserve">Abstract</x> Experimental studies of fatigue of composite laminates have clarified the progressive mechanisms underlying this phenomenon. These mechanisms cause degradation in load bearing capacity of laminates and failure occurs when the residual strength equals the maximum applied stress. Assuming that the strength degradation can be related to a measure of the fatigue damage, a two‐stage reliability model is developed. A three‐parameter Weibull distribution is assumed to describe the initial strength and the probability distributions of residual strengths in both stages and of the fatigue life are derived from this distribution. Experimental data are analyzed to support the results.